PERANCANGAN PRIVATE CLOUD STORAGE PADA UNIVERSITAS ADIWANGSA JAMBI - santoso, santoso; Tandy, Juliana; Siagian, Saut; Husni, Akhmad Faisal (JOURNAL V-TECH (VISION TECHNOLOGY), 2020)
Storage media evolve from time to time, from small capacity diskettes to large capacity hard disks. All adjust the needs, which is the development of software increasing storage space (storage) needed. But in this day and age the effectiveness and efficiency of using storage is the user's choice. Cloud storage has advantages in terms of scalability or the use of storage can be adjusted to the needs of the user side itself, besides that from the IT administration side because all activities are centralized on the server, adding storage capacity can be quickly, system improvements can be done easily and costs are far smaller than replacing hardware resources in many places. a service that is able to effectively and efficiently handle the need for cloud storage at Adiwangsa Jambi University. In this study the aim is to design cloud storage architecture at the Adiwangsa Jambi University using the waterfall method. The design is done by making a relational database system gives good results and is suitable for further development.